Iron(III) Complexes with Substituted Salicylaldehydes: Synthesis, Interaction with DNA and Serum Albumins, and Antioxidant Activity - Zisis Papadopoulos; Antonios G. Hatzidimitriou; George Psomas (Molecules)
Metal complexes of endogenous metals, such as iron, copper, and zinc, offer a biocompatible, cost-effective, and eco-friendly alternative to heavy metals for drug design. This study presents the synthesis, structural characterization, and evaluation of the biological activity of eight novel iron(III) complexes with substituted salicylaldehydes as ligands. The characterization of the complexes involved spectroscopic and physicochemical methods. The structures of two complexes were determined using single-crystal X-ray crystallography. The biological studies of the complexes focused on the interaction of calf-thymus DNA, the (photo)cleavage of pBR322 plasmid DNA (pDNA), the affinity for bovine and human serum albumins, and the antioxidant activity. The complexes interacted with calf-thymus DNA via intercalation with high DNA-binding constants. The complexes exhibited high pDNA-cleavage ability, which is significantly enhanced upon exposure to UVA or UVB irradiation. The complexes can bind tightly and reversibly to both serum albumins, and their binding locations were identified. Finally, the complexes showed moderate ability to scavenge 1,1-diphenyl-picrylhydrazyl and 2,2′-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) radicals with a high ability to reduce hydrogen peroxide.